[Baguio salvaging ; The Reddening sea ; Proving them wrong [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Myrna Diones the lone survivor of the torture and murder of four girls along Naguilian Road tells Probe Team about the ordeal. Political issues on Red Tide. A visit at Camp John Hay to see if has deteriorated.